a) 13 x A + 5 x B + 13 x B + 5 x A
= ( 13 x A + 13 x B ) + ( 5 x B + 5 x A )
= 13 x ( A + B ) + 5 x ( B + A ) mà A + B = 12
=> 13 x ( A + B ) + 5 x ( B + A )
= 13 x 12 + 5 x 12
= 12 x ( 13 + 5 )
= 12 x 18
= 216
b) 4 x A + 25 x B + 16 x A - 5 x B
= ( 4 x A + 16 x A ) + ( 25 x B - 5 x B )
= A x ( 4 + 16 ) + ( 25 - 5 ) x B
= A x 20 + 20 x B
= 20 x ( A + B ) mà A + B = 12
=> 20 x ( A + B )
= 20 x 12
= 240
Trả lời :
a) 13 x A + 5 x B + 13 x B + 5 x A
= 13 x (A + B)+ 5 x (A + B)
= (13 x 12) + (5 x 12)
= 156 + 60
= 216
b) 4 x A + 25 x B + 16 x A - 5 x B
= 25 + 4 x (A + B) + 16 - 5 x (A + B)
= 29 x 12 + 11 x 12
= 348 + 132
= 480
T i c k nha !!